Measuring gender equality practices in the workplace: a focus on UN global compact network Bangladesh member companies and external private sector businesses in Bangladesh - Abdullah, Ayesha Tomalea (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.